Comparative evaluation of two cetylpyridinium chloride-based mouthwashes on the mechanical properties and strength loss of elastomeric chains used in dentistry: An vitro study - Carolina Andrés Castelló; Natalia Zamora-Martínez; Beatriz Tarazona-Álvarez; Vanessa Paredes-Gallardo (Heliyon, 2024)
Objectives: Evaluate the strength degradation of polymeric ligature chains after their immersion in cetylpyridinium chloride-based mouthwashes. Methods: 240 elastomeric samples from four different manufacturers (Rocky Mountain®, Ormco®, Morelli® and Dentaurum®) in two types of configurations (with and without intermodular links) and divided in 3 groups (distilled water, Vitis CPC Protect® and PERIO·AID® 0.05%) at 5 follow-up periods (0–24 h, 7–14 -21 days) were immersed twice a day for 60 s, following the manufacturers' protocols. A universal traction machine was used to perform the measurements and a post hoc multiple comparisons were based on the Bonferroni test and extended to a 3-way ANOVA test (α = 0.05). Results: There was a drop in strength up to 35.9% at 24 h. After a week, the short chains (52%) degraded less than the long ones (57.3%) with significant differences (p < 0.001) and the same pattern was observed until 21 days (p < 0.001). At 24 h, the degradation of the chains exposed in distilled water was 25.8%, in VITIS CPC Protect® 28.6% and in PERIO· AID® 0.05%, 27% with significant differences (p < 0.001). At 21 days, the VITIS CPC Protect® group obtained a much greater loss of strength, being this drop statistically significant (p < 0.001). The chains from Ormco® and RMO® experienced the least loss of force when immersed in the control group or PERIO AID® 0 0.05% (48% and 51%), while Dentaurum's in VITIS CPC Protect® lost more than 75%. Conclusions: The orthodontic elastomeric chains suffer a sharp drop in strength during the first days of treatment. When comparing the mouthwashes, there were statistically significant differences in terms of strength degradation. Clinical significance: Based on the results, some types of chains, such as the ones without intermodular links from Ormco® showed better properties throughout the study. When immersed in PERIO·AID®0.05%, all showed significantly better results over time. Thus, PERIO·AID®0.05% can be recommended as a complementary oral hygiene element in dental treatments when elastomeric chains are used.